(3cJGH aj JHjGf GNJdGa JfRjd GdbQBfs
(3ChdgG (B:s
(3GdMeO ddg GdCMO HdGYOO CeG HYO agPg cdeGJ LeYJgG ai JHjGf ENJdGa JfRjd GdbQBf hTQMgG hHSWgG s
(3BNQgG (B:s
(3hLedI GdcdGe SHY hSHYhf Gda cdeI hCQHYeGFI hCQHY hKdGKhf cdeI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B63s
(3HgG fXGe GdJYbjHIs
(3cJHJ CSeGA GdShQ ajgG HGdMeQIs
(3Ydi GdfSNI JedcGJ CbOegG SfI (B1016(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs